1211 An Ameloblastoma Or Intra-Oral Basal Cell Carcinoma? A Clinical Case Report. (12th October 2021) - Crummey, S; Amini, A
Abstract: A basal cell ameloblastoma is an uncommon benign neoplasm and has a similar histological appearance to basal cell carcinoma of the skin. This clinical case report will discuss an ameloblastoma originating in the maxilla and of the baseloid variant. The objective of report is to highlight the possibility of misdiagnosis from this challenging case. A 34-year-old male was referred to the maxillofacial department with recurrent nasal regurgitation following dental extraction from the left maxilla 1 year previous. Clinically there was an oro-antral fistula visible and initial CT showed cystic lesion in the left maxilla likely to represent an odontogenic cyst. The patient underwent extraction and enucleation, where the diagnosis of the amelobalstoma was established with need of resection. Partial maxillectomy and primary closure with buccal fadpad was performed in the second stage and histological results showed a 6mm completely excised basal cell carcinoma within the oral mucosa and no bony invasion. Due to this extremely unusual results, secondary histological review was requested, and conclusion was a fully excised basal cell ameloblastoma. Following the procedure and subsequent reviews, the patient has no evidence of oro-antral fistula or recurrence of this rare type of neoplasm. A basal cell ameloblastoma variant is a rare lesion and due to its' similar histological appearance to a basal cell carcinoma, can lead to a misdiagnosis. The aim of the report is to show the unusual presentation and findings along the way to correct diagnosis in this case.